Follow-up after rectal cancer: developing and testing a novel patient-led follow-up program. Study protocol. (1st February 2017) - Hovdenak Jakobsen, Ida; Juul, Therese; Bernstein, Inge; Christensen, Peter; Jensen, Frank Svendsen; Johansen, Christoffer; Lindhardt Larsen, Susie; Laurberg, Søren; Madsen, Mogens Rørbæk; Thorlacius-Ussing, Ole; Vind Thaysen, Henriette
Abstract: Background: The main treatment for non-metastatic rectal cancer (RC) is surgical resection. Late adverse effects that are highly prevalent and negatively impact patients' symptom burden and quality of life are: bowel-, urological and sexual dysfunctions; psychological distress; fear of recurrence. Patients and clinicians have requested a more patient-centred follow-up, balancing the focus on detection of recurrence, and physiological and psychological late adverse effects. The current follow-up program primarily focuses on detection of recurrence, with less attention on late adverse effects. As a consequence, the randomized controlled trial Follow-up after Rectal Cancer (FURCA) has been launched, testing the effect of a new patient-led, follow-up program. The aim of this paper is to describe the methodology used in the FURCA study and to report results from the development of the patient-led, follow-up program. Adult patients, treated with curative intent for primary adenocarcinoma in the rectum are included from four Danish centers. Material and methods: Patients are randomized into an intervention group, receiving standardized education and access to self-referral to an assigned project nurse, or a control group following the current follow-up program with routine medicals. The primary outcomes are symptom burden and quality of life, measured by the Functional Assessment of Cancer Therapy – Colorectal (FACT-C) questionnaire. Other outcome and demographic data are collected as patient-reported measures and register-based data. Results from developing the intervention: The education program is based on data from two focus group interviews and the feedback from experts. An algorithm is developed in order to qualify the research nurses' responses to patients' self-referral. Discussion and perspectives: The results of the FURCA study will strengthen the evidence base for RC follow-up, and qualify the ongoing transformation in cancer follow-up programs.